Height and weight-adjusted intrathecal 0.5% hyperbaric Bupivacaine for elective cesarean section: an outcome analysis in a rural Nepal tertiary centre - Khapung, Robin; Basnyat, Subi; Thapa, Nabin; Giri, Praveen Kumar; Bhatterai, Ramesh; Bhandari, Jeetendra; Shrestha, Prerana; Banjade, Subika; Pandey, Alan; Adhikari, Apil; Limbu, Poshan Samser; Silwal, Shirish; et al. (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Spinal anesthesia with 0.5% hyperbaric bupivacaine is preferred for cesarean section(CS) but often causes maternal hypotension with potential fetal effects. Using Harten’s chart to dose based on height and weight may limit block height and reduce hypotension. We compared fixed-dose and adjusted regimens.Method: This prospective observational study at Karnali Academy of Health Sciences (Aug–Dec 2022) included 58 term singleton ASA II women undergoing elective CS. Intrathecal 0.5% hyperbaric bupivacaine was given as either fixed dose (11 mg) or Harten’s chart–calculated dose. Primary outcome was change in mean arterial pressure; secondary outcomes were systolic blood pressure, heart rate, block characteristics, vasopressor use, and adverse effects. Significance was P < 0.05.Result: Adjusted-dose group received lower median intrathecal dose than fixed-dose group (9 mg [IQR 8.5–9.5] vs 11 mg; P